Late side-effects and cosmetic results of accelerated partial breast irradiation with interstitial brachytherapy versus whole-breast irradiation after breast-conserving surgery for low-risk invasive and in-situ carcinoma of the female breast: 5-year results of a randomised, controlled, phase 3 trial - Polgar, Csaba; Ott, Oliver J.; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Lyczek, Jaroslaw; Guinot, Jose Luis; Dunst, Jurgen; Miguelez, Cristina Gutierrez; Slampa, Pavel; Allgaeuer, Michael; et al. (Lancet Oncology, 2017)
BACKGROUND: We previously confirmed the non-inferiority of accelerated partial breast irradiation (APBI) with interstitial brachytherapy in terms of local control and overall survival compared with whole-breast irradiation for patients with early-stage breast cancer who underwent breast-conserving surgery in a phase 3 randomised trial. Here, we present the 5-year late side-effects and cosmetic results of the trial. METHODS: We did this randomised, controlled, phase 3 trial at 16 centres in seven European countries. Women aged 40 years or older with stage 0-IIA breast cancer who underwent breast-conserving surgery with microscopically clear resection margins of at least 2 mm were randomly assigned 1:1, via an online interface, to receive either whole-breast irradiation of 50 Gy with a tumour-bed boost of 10 Gy or APBI with interstitial brachytherapy. Randomisation was stratified by study centre, menopausal status, and tumour type (invasive carcinoma vs ductal carcinoma in situ), with a block size of ten, according to an automated dynamic algorithm. Patients and investigators were not masked to treatment allocation. The primary endpoint of our initial analysis was ipsilateral local recurrence; here, we report the secondary endpoints of late side-effects and cosmesis. We analysed physician-scored late toxicities and patient-scored and physician-scored cosmetic results from the date of breast-conserving surgery to the date of onset of event. Analysis was done according to treatment received (as-treated population). This trial is registered with ClinicalTrials.gov, number NCT00402519. FINDINGS: Between April 20, 2004, and July 30, 2009, we randomly assigned 1328 women to receive either whole-breast irradiation (n=673) or APBI with interstitial brachytherapy (n=655); 1184 patients comprised the as-treated population (551 in the whole-breast irradiation group and 633 in the APBI group). At a median follow-up of 6·6 years (IQR 5·8-7·6), no patients had any grade 4 toxities, and three (<1%) of 484 patients in the APBI group and seven (2%) of 393 in the whole-breast irradiation group had grade 3 late skin toxicity (p=0·16). No patients in the APBI group and two (<1%) in the whole-breast irradiation group developed grade 3 late subcutaneous tissue toxicity (p=0·10). The cumulative incidence of any late side-effect of grade 2 or worse at 5 years was 27·0% (95% CI 23·0-30·9) in the whole-breast irradiation group versus 23·3% (19·9-26·8) in the APBI group (p=0·12). The cumulative incidence of grade 2-3 late skin toxicity at 5 years was 10·7% (95% CI 8·0-13·4) in the whole-breast irradiation group versus 6·9% (4·8-9·0) in the APBI group (difference -3·8%, 95% CI -7·2 to 0·4; p=0·020). The cumulative risk of grade 2-3 late subcutaneous tissue side-effects at 5 years was 9·7% (95% CI 7·1-12·3) in the whole-breast irradiation group versus 12·0% (9·4-14·7) in the APBI group (difference 2·4%; 95% CI -1·4 to 6·1; p=0·28). The cumulative incidence of grade 2-3 breast pain was 11·9% (95% CI 9·0-14·7) after whole-breast irradiation versus 8·4% (6·1-10·6) after APBI (difference -3·5%; 95% CI -7·1 to 0·1; p=0·074). At 5 years' follow-up, according to the patients' view, 413 (91%) of 454 patients had excellent to good cosmetic results in the whole-breast irradiation group versus 498 (92%) of 541 patients in the APBI group (p=0·62); when judged by the physicians, 408 (90%) of 454 patients and 503 (93%) of 542 patients, respectively, had excellent to good cosmetic results (p=0·12). No treatment-related deaths occurred, but six (15%) of 41 patients (three in each group) died from breast cancer, and 35 (85%) deaths (21 in the whole-breast irradiation group and 14 in the APBI group) were unrelated. INTERPRETATION: 5-year toxicity profiles and cosmetic results were similar in patients treated with breast-conserving surgery followed by either APBI with interstitial brachytherapy or conventional whole-breast irradiation, with significantly fewer grade 2-3 late skin side-effects after APBI with interstitial brachytherapy. These findings provide further clinical evidence for the routine use of interstitial multicatheter brachytherapy-based APBI in the treatment of patients with low-risk breast cancer who opt for breast conservation. FUNDING: German Cancer Aid.
EVALuna2:32911